2021
DOI: 10.1021/acsomega.1c04166
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Thermal Decomposition of 3,4-Bis(3-nitrofurazan-4-yl)furoxan

Abstract: When stimulated, for example, by a high temperature, the physical and chemical properties of energetic materials (EMs) may change, and, in turn, their overall performance is affected. Therefore, thermal stability is crucial for EMs, especially the thermal dynamic behavior. In the past decade, significant efforts have been made to study the thermal dynamic behavior of 3,4-bis(3-nitrofurazan-4-yl)furoxan (DNTF), one of the new high-energy-density materials (HEDMs). However, the thermal decomposition mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The decomposition pathways of furoxans are significant to the developments of furoxan based high energetic materials and a series of computational studies have been applied to investigate the decomposition or pyrolysis mechanism of energetic furoxan structures. [28][29][30][31][32] Recently, we fully reported our theoretical research on the decompositions of BTFT structure, including the initial unimolecular decomposition of BFTF from quantum mechanics calculations and ReaxFF molecular dynamics simulation. Our reactive molecular dynamics simulations showed that NO 2 would be the initial product and further theoretical research confirmed that the decomposition of BFTF starts from the nitro moieties in fluorodinitromethyl groups followed by furoxan ring openings.…”
Section: Resultsmentioning
confidence: 99%
“…The decomposition pathways of furoxans are significant to the developments of furoxan based high energetic materials and a series of computational studies have been applied to investigate the decomposition or pyrolysis mechanism of energetic furoxan structures. [28][29][30][31][32] Recently, we fully reported our theoretical research on the decompositions of BTFT structure, including the initial unimolecular decomposition of BFTF from quantum mechanics calculations and ReaxFF molecular dynamics simulation. Our reactive molecular dynamics simulations showed that NO 2 would be the initial product and further theoretical research confirmed that the decomposition of BFTF starts from the nitro moieties in fluorodinitromethyl groups followed by furoxan ring openings.…”
Section: Resultsmentioning
confidence: 99%
“…For DNTF and other furazan compounds, the unpaired electrons of atoms in the furazan ring form a conjugated π bond, which elongates the N–O bond length. Additionally, the furoxan ring exhibits strong electrophilic behavior owing to the oxygen atom outside the ring, leading to further elongation of the N–O bond .…”
Section: Methodsmentioning
confidence: 99%
“…The decomposition pathways of furoxans are significant to the developments of furoxan based high energetic materials and a series of computational studies have been applied to investigate the decomposition or pyrolysis mechanism of energetic furoxan structures [33][34][35][36][37]. Recently, we fully reported our theoretical research on the decompositions of BTFT structure, including the initial unimolecular decomposition of BFTF from quantum mechanics calculations and ReaxFF molecular dynamics simulation.…”
Section: T P4 267mentioning
confidence: 99%